2020
DOI: 10.1007/s00224-020-09967-8
|View full text |Cite
|
Sign up to set email alerts
|

Token Sliding on Split Graphs

Abstract: We consider the complexity of the Independent Set Reconfiguration problem under the Token Sliding rule. In this problem we are given two independent sets of a graph and are asked if we can transform one to the other by repeatedly exchanging a vertex that is currently in the set with one of its neighbors, while maintaining the set independent. Our main result is to show that this problem is PSPACE-complete on split graphs (and hence also on chordal graphs), thus resolving an open problem in this area.We then go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Lokshtanov and Mouawad [25] showed that, in bipartite graphs, Token Jumping is NP-complete while Token Sliding remains PSPACE-complete. In split graphs, Token Jumping is a trivial problem while Token Sliding is PSPACE-complete [2]. In addition to the classes above, Token Jumping can be decided in polynomial time for even-hole-free graphs [21].…”
Section: :3mentioning
confidence: 99%
“…Lokshtanov and Mouawad [25] showed that, in bipartite graphs, Token Jumping is NP-complete while Token Sliding remains PSPACE-complete. In split graphs, Token Jumping is a trivial problem while Token Sliding is PSPACE-complete [2]. In addition to the classes above, Token Jumping can be decided in polynomial time for even-hole-free graphs [21].…”
Section: :3mentioning
confidence: 99%
“…Even on bipartite graphs, VCR remains PSPACE-complete under TS, and NP-complete under each of TJ and TAR [20]. On chordal graphs, VCR is known to be PSPACE-complete under TS [4]. On the positive side, polynomialtime algorithms have been designed for VCR on even-hole-free graphs (and therefore chordal graphs) under each of TJ and TAR [18], on bipartite permutation graphs and bipartite distance-hereditary graphs [12] under TS, on cographs [6,18], claw-free graphs [7], interval graphs [5,18], and trees [10,18] under each of TS, TJ, and TAR.…”
Section: Introductionmentioning
confidence: 99%
“…Our goal is to find a sequence of independent sets that represents a step-by-step modification from one of the given independent sets to the other. There are three local modification rules studied in the literature: Token Addition and Removal (TAR) [3,19,22], Token Jumping (TJ) [4,5,16,17,18], and Token Sliding (TS) [1,2,8,10,13,15,21]. Under TAR, given a threshold k, we can remove or add any vertices as long as the resultant independent set has size at least k. (When we want to specify the threshold k, we call the rule TAR(k).)…”
Section: Introductionmentioning
confidence: 99%
“…For claw-free graphs, the problem is solvable in polynomial time under all three rules [4]. For even-hole-free graphs (graphs without induced cycles of even length), the problem is known to be polynomial-time solvable under TAR and TJ [19], while it is PSPACE-complete under TS even for split graphs [1]. Under TS, forests [8] and interval graphs [2] form maximal known subclasses of even-hole-free graphs for which Independent Set Reconfiguration is polynomial-time solvable.…”
Section: Introductionmentioning
confidence: 99%